2020
DOI: 10.31729/jnma.4815
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge on Diet among the Hypertensive Patients in a Tertiary Care Center Nepal: A Descriptive Cross-sectional Study

Abstract: Introduction: Hypertension is one of the leading causes of death and disability in both developed and developing countries. The prevalence of hypertension is increasing rapidly worldwide. The aim of the study was to determine the knowledge of diet and exercise among hypertensive patients. Methods: This descriptive cross-sectional study was conducted using a structured questionnaire among 169 hypertensive patients at Kathmandu diabetes and thyroid center from May 2017 to July 2017 after taking ethical cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 6 publications
0
4
0
1
Order By: Relevance
“…In Ethiopia, Kebede et al (14) reported that more than half of participant hypertensive patients were males (53.5%), with a mean age of 50 years. However, the study of Maharjan et al (13) reported that the prevalence of hypertension was higher among females than males.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…In Ethiopia, Kebede et al (14) reported that more than half of participant hypertensive patients were males (53.5%), with a mean age of 50 years. However, the study of Maharjan et al (13) reported that the prevalence of hypertension was higher among females than males.…”
Section: Discussionmentioning
confidence: 94%
“…Most studies indicated that the majority of the participants were aged 50 years, in the USA (11); Egypt (12); and Nepal (13). In Ethiopia, Kebede et al (14) reported that more than half of participant hypertensive patients were males (53.5%), with a mean age of 50 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Tỷ lệ đối tượng nghiên cứu có kiến thức về CĐDD đạt là 74,8%. Tỷ lệ này cao hơn nghiên cứu của Đỗ Minh Sinh và nghiên cứu của Nguyễn Văn Tuấn (Đỗ Minh Sinh et al, 2018;Nguyễn Văn Tuấn và Trần Thị Anh Thơ, 2021) hay nghiên cứu ngoài nước của tác giả Nabina Maharjan (Nabina Maharjan et al, 2017).…”
Section: Bàn Luậnunclassified
“…According to Azrimaidaliza et al ( 2018), improving the quality of life for hypertension sufferers requires information regarding proper food management. According to Maharjan (2020), he also stated that education about hypertension diet is very necessary to increase awareness and regulate appropriate diet.…”
Section: Providing Hypertension Diet Educationmentioning
confidence: 99%